WAYS TO TEACH ENTREPRENEURIAL CULTURE TO STUDENTS (The Conference Hub, 2025)
This article examines modern approaches and ways to develop an entrepreneurial culture in students at higher education institutions. It explores the importance of entrepreneurial thinking as a crucial factor in professional self-realization in a market economy. Pedagogical conditions, methods, and forms of teaching that promote initiative, responsibility, and innovation in students are identified.